Analysis of the Influence of Oil and Gas Exports, Non-Oil and Gas Exports, Rupiah Exchange Rate, and Domestic Investment on Economic Growth in Indonesia - Cahyaningsih, Dini; Khasanah, Uswatun; Nasir, Muhammad Safar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the variables that affect economic growth. This study uses a time series model, namely multiple linear regression. Research data obtained from the Central Bureau of Statistics from 1997 to 2022. The results of the study are that non-oil and gas exports have a significant positive effect on economic growth, the Rupiah exchange rate has a significant negative effect on Indonesia's economic growth. While Domestic Investment and Oil and Gas Exports together do not have a significant effect on Indonesia's economic growth